Covid-19 Lockdown and The Plights of People Remanded in Security Detention Centres: A Socio Legal Analysis - Maigari, Abdullahi Muhammad; Dauran, Faruk Usman; Qadir, Uthman Abdullahi Abdul- (Walisongo Law Review (Walrev), 2022)
The researchers analyzed from sociological and legal perspectives the COVID-19 lockdown and the plights of people remanded in security detention centers in Nigeria. The objective of the study is to identify the loopholes in the Constitution of the Federal Republic 1999 as amended and other relevant legal provisions in Nigeria. The study is an exploratory type of research whose goal is to explore the phenomenon under investigation. This research design is considered appropriate for this paper because the COVID-19 lockdown has explored the weaknesses of the extant legal provisions in Nigeria in a situation like the Lockdown. Data were from secondary sources and were subjected to content analysis. The result revealed that during the COVID-19 lockdown in Nigeria, accused persons, awaiting trial persons and prisoners in different detention centers were detained beyond the legal requirements whereas there is no legal provision that clearly stated remedies.Tulisan ini mengkaji hak-hak orang yang ditahan oleh aparat keamanan atau dijebloskan ke dalam lembaga pemasyarakatan oleh Pengadilan sebelum lockdown COVID-19 dan menjalani masa karantina COVID-19 dalam tahanan. Para peneliti mengidentifikasi ketentuan hukum yang terkandung dalam Konstitusi Republik Federal Nigeria 1999 & celah di dalamnya yang gagal membuat ketentuan untuk keadaan darurat seperti penguncian. Konsekuensi yang tidak diinginkan dari tindakan purposive oleh Robert Merton diadopsi sebagai penjelasan teoretis. Makalah ini mengadopsi desain penelitian eksplorasi untuk mengeksplorasi kekosongan dalam Hukum Nigeria di mana data bersumber dari sumber sekunder dalam teks terdokumentasi. Makalah ini menemukan bahwa semua Undang-undang dan Undang-undang di Nigeria tidak memiliki ketentuan tentang bagaimana memberi kompensasi kepada orang-orang yang mengalami masalah emosional, keuangan sosial, dan psikologis sebagai akibat dari waktu yang mereka habiskan di sel tahanan di luar waktu yang diharapkan karena penguncian.